Estudo da modelagem do transporte de sedimentos da Baía de Vitória-ES e potenciais alterações na dinâmica hidrossedimentológica mediante o aprofundamento do canal estuarino - Lacerda, Kaio Calmon (2022)
Several studies have been carried out on the possible impacts of natural changes or anthropic interventions in coastal systems, such as the relative rise in sea level, landfills and dredging. Numerical modeling stands out as a key method for allowing hypotheses to be tested in addition to providing assertive results with high spatial and temporal resolution. Potential impacts of the deepening project of the Vitória Port channel, concluded in 2017, are investigated using the numerical hydrodynamic and sediment transport model Delft3D, three-dimensional (3D), forced by tide, wind, atmospheric pressure and thermohaline gradients. The numerical model reproduced well the observed elevation, velocity, temperature, salinity and Suspended Sediment Concentration (SSC) data in Vitória Bay. In addition, the importance of using a 3D model for the present study was pointed out by the gradients of variables identified in the water column, with greater emphasis on velocity and, consequently, on the shear stress at the bottom. The surface composition based on the percentages of cohesive and non-cohesive sediment was the one that presented the most satisfactory results among the bottom composition approaches evaluated in the sediment transport model. Furthermore, the experiments in which the temporal variation of the model parameters along the spring and low tide cycles were considered allowed to obtain better results. This was observed by the smaller error values obtained in relation to the available measured data, but without significantly overestimating the average and maximum concentration values indicated by the measured data reported in the literature for the area. A 3D model was considered in which the erosion parameter (kg/m2/s) varied from 5x10-6 (spring) to 30x10-6 (neap) with an TCE of 0.2 N /m2 for the experiment that presented the most satisfactory results. Regarding the deepening considered, from the velocity series it was possible to observe that the impact on the velocities varies throughout the neap-spring tidal cycle, in addition to presenting distinct patterns along the water column. Despite the statistical parameters pointing to trends in the average impact that deepening has on hydrodynamic patterns throughout the study area, the results indicate that this pattern varies over time and along the water column. Therefore, considering the analysis of the hydrodynamic results, it was not possible to establish an expected pattern of impact on the transport of sediments in the region. However, based on the sediment transport simulations carried out, it can be concluded that, for the simulated conditions and the considered deepening, in general, there is a reduction in resuspension fluxes along the bay, with a consequent reduction in SSC and eroded volume along the study area. The results indicate a reduction of 4.3% in the total volume of material eroded, considering the entire study area, as a result of the deepening and a percentage reduction in the average SSC of up to 20% in the evaluated stations